Divining A Decolonial Future: Mythopoesis As A Force Of Resistance In Margaret Laurence’s The Diviners - Dr. Eleanor Vance (International Journal Of History And Political Sciences, 2025)
BACKGROUND: Postcolonial literature often grapples with the task of reclaiming identity from the lingering shadows of colonial narratives. In the Canadian context, this involves confronting a colonial history that has suppressed Indigenous and non-British voices. Margaret Laurence’s The Diviners stands as a seminal work in this tradition, employing myth not as a static relic, but as a dynamic tool for cultural and personal reconstruction. OBJECTIVE: This article examines how Margaret Laurence utilizes myth as a decolonial force in The Diviners. It argues that the novel’s protagonist, Morag Gunn, engages in a process of mythopoesis—the conscious creation of myth—to dismantle colonial frameworks and construct an inclusive, decolonized identity that embraces her complex Scottish and Métis heritage. METHODS: This study employs a qualitative textual analysis, drawing upon postcolonial and decolonial theories as articulated by scholars such as Homi K. Bhabha, Edward Said, and Walter D. Mignolo, alongside theories of myth from Northrop Frye and Carl Jung. The analysis focuses on the interplay between personal memory, historical narrative, and folkloric traditions within the novel. RESULTS: The analysis reveals three primary layers of myth in The Diviners: the inherited Scottish legends of Piper Gunn, the suppressed Métis stories of Jules Tonnerre, and Morag’s own personal myths forged through her experiences. The study finds that Laurence deliberately braids these mythological threads to challenge the singular, linear history imposed by colonialism, creating a "third space" where marginalized histories can be voiced and validated. CONCLUSION: The Diviners serves as a powerful example of how literature can enact decolonization. By weaving together disparate myths, Laurence demonstrates that identity is not a fixed inheritance but a continual process of "divining"—of interpreting the past to create new, liberatory narratives for the future. The novel’s ultimate power lies in its transformation of myth from a tool of colonial ideology into a potent vehicle for resistance and cultural survivance.